Mirage in Thi-Rrummah's Poems: Unique Images in the Arabic Poetry- An Aesthetic and cultural Study (Journal of Hama University, 2019)
The images of mirage in the poems of (ZeArrema) formed a unique feature in the Arabic poetry.The images of mirage in the poems of (ZeArrema) formed a unique feature in the Arabic poetry.This research aims to show the sides particularity of this poet following an inductive, statistical process that enables us to say a lot about the particularity and quantitative in the images of mirage within his poetry.The curriculum showed o lot of innovative sides in both mental and technical levels during building mirage images .The cultural curriculum revealedto us the link of mirage phenomenon at the poet with the cultural patterns which belong to the ancient Arabic poetry and his expertise .It also explained the aesthetic approach demonstrating the aesthestic value of the mirage phenomenon and embodiment of the concept of magnificence intellectually and artistically.These approaches have integrated to build a vital study covering aesthestic and intellectual structures in which (ZeArrema) contributed to create the images of mirage and his unqueness from his contemporaries and formers.He formed the (  Mirage ) documenting life and phenomenon of desert , the ways of conflict that the Arabs used against the environment and the methods of defeating it,the victory of life .He revealed the moral and artistic vision through the embodiment of mirage in reality and poetry making these poems  a record for the environment phenomenon from one side ,and an artistic mask to his experience in